2021
DOI: 10.1016/j.urolonc.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers in bladder cancer: A review of the current landscape and future directions

Abstract: ActionAdobe Reader version 9 Adobe Reader version X and XI Insert textClick the 'Text Edits' button on the Commenting tool bar. Click to set the cursor location in the text and simply start typing. The text will appear in a commenting box. You may also cut-and-paste text from another file into the commenting box. Close the box by clicking on 'x' in the top right-hand corner.Click the 'Insert Text' icon on the Comment tool bar. Click to set the cursor location in the text and simply start typing. The text will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 85 publications
5
120
0
Order By: Relevance
“…It is important to highlight the significance of these results in comparison to other urinary biomarkers for bladder cancer 5,19,29–33 . We have confirmed that URO17™ has one of the highest sensitivity and specificity reported in identifying bladder cancer through noninvasive urine samples.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…It is important to highlight the significance of these results in comparison to other urinary biomarkers for bladder cancer 5,19,29–33 . We have confirmed that URO17™ has one of the highest sensitivity and specificity reported in identifying bladder cancer through noninvasive urine samples.…”
Section: Discussionsupporting
confidence: 69%
“…It is important to highlight the significance of these results in comparison to other urinary biomarkers for bladder cancer. 5,19,[29][30][31][32][33] We have confirmed that URO17™ has one of the highest sensitivity and specificity reported in identifying bladder cancer through non- and expands the application of URO17™ to hematuria patients. In the end, combinations of biomarkers may be the key to providing the most effective investigation where the application of URO17™…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This is probably due to the fact that new biomarkers demonstrating high efficiency in research laboratories are not sufficiently reliable when used for screening a large number of patients. The relevance of the topic is confirmed by a large number of articles and reviews published in recent years, for example ( Maas et al, 2019 ; Ng et al, 2020 ; Chakraborty et al, 2019 ; Kim et al, 2020 ; Batista et al, 2020 ; Faiena et al, 2019 ; Matuszczak and Salagierki, 2020 ; Miyamoto et al, 2020 ; Carando et al, 2021 ). The authors are constantly systematizing and analyzing new data to select biomarkers for both diagnosing BC and monitoring treatment response.…”
Section: Introductionmentioning
confidence: 92%